Pharmacognostic Characteristics of Hibiscus sabdariffa L. as a Means of Monitoring Quality - Emelia Oppong Bekoe*; Cindy Kitcher; Gladys Agyei; Samuel Frimpong-Manso (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Hibiscus sabdariffa L. (roselle) sepals, commonly known as bissap is prepared as a cold drink which is widely drunk in Ghana and across West-Africa for their medicinal and nutritional properties. The plant is known to have anti-hypertensive, anti-hyperlipidemic, anticancer, anti-diabetic and anti-inflammatory activities. For such a widely sold and used medicinal plant, it is important that simple but reliable parameters can be used to estimate the quality. This will reduce adulteration, improve quality and hence safeguard the consumer. This study was to examine simple parameters that can be employed to estimate the quality of dried whole and powdered samples of H. sabdariffa that are widely sold on the open West-African market. Methods: The parameters investigated were macroscopic, microscopic, phytochemical, physicochemical, microbiological, and fluorescence characteristics. Heavy metal and HPLC analyses were also performed. Results: The sepals of H. sabdariffa were dark red, united sepals alongside valvate aestivation. Phytochemical analysis showed the presence of saponins, tannins, alkaloids, flavonoids, and glycosides. It exhibited unique fluorescent profiles in various reagents. HPLC fingerprint showed 7 peaks eluting within 1 and 5 minutes. Arsenic, lead, mercury, and chromium were not detected but cadmium was detected which was within acceptable limits. The aerobic bacteria and fungi count were also within acceptable limits. Conclusion: These parameters can be used to evaluate the quality of dried sepals of Hibiscus sabdariffa sold on the open market before they are used in the manufacturing of beverages and medicines.